Seasonal dynamics of bean aphids and its relationship with the abundance of Lady Bird Beetles (Bangladesh Journal of Zoology, 2021)
The seasonal dynamics of aphid Aphis craccivora Koch (Hemiptera: Aphididae) on four bean species namely country bean Lablab purpureus, yard long bean Vigna sesquipedalis, hyacinth bean Dolichos lablab and bush bean Phaseolus vulgaris were studied from September to December 2017 in the experimental field of the Department of Entomology, Bangabandhu Sheikh Mujibur Rahman Agricultural University, Gazipur, Bangladesh. The study also investigated the relationship between the abundance of aphid and its predatory insect lady bird beetle. Aphid abundance on the bean species showed increasing trend from the 4th week of September and reached to the peak during the 2nd week of November and then declined. Bush bean and yard long bean, respectively depicted the higher and lower abundances of aphid throughout the study. Relationship between the abundance of aphid and lady bird beetle on the bean species were positively correlated. Aphid showed negatively correlation with temperature and rainfall, and positive correlation with relative humidity, and the correlations were not significant. Multiple regression equation showed that temperature had the highest effect which contributed 16.1 - 19.2% role on the population of aphid.Bangladesh J. Zool. 48(2): 357-363, 2020